Coping of adolescents and young adults with ADHD symptoms in school and workplace - Krauss, Annette; Mackowiak, Katja (Swiss Journal of Educational Research, 2023)
In the present study, the ability of adolescents and young adults with varying degrees of ADHD symptoms to cope with demands was investigated with quantitative and qualitative methods. 907 adolescents and young adults between the ages of 14 and 24 years from vocational and baccalaureate schools in the German-speaking part of Switzerland were asked to fill out a questionnaire in class. In addition, three episodic interviews were conducted with adolescents affected by ADHD. The results suggest that those affected have greater difficulties in coping with academic and occupational demands than unaffected adolescents and that, among other things, unfavourable learning and working conditions at school and in the workplace can have an inhibiting effect on coping with demands.